Efektivitas Metode Daring terhadap Hasil Belajar Siswa Mata Pelajaran Bahasa Indonesia di Kelas II SDN 104214 TA. 2020/2021 - Desna Fitriana Br. Barus; Rizka Hidayah Husin Lubis (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2021)
This study aims to evaluate the effectiveness of online versus face-to-face teaching methods in the learning process of the Indonesian language subject for second-grade students at SDN 104214 during the 2020/2021 academic year. The method used is a quasi-experimental design with two groups: experimental and control. Instruments used include pretests and posttests to measure learning outcomes and an observation sheet for implementation of learning. The findings indicate that face-to-face teaching methods are more effective than online methods, as seen from the significant differences in the average post-test scores between the control and experimental groups. Additionally, observations show deficiencies in the implementation of online methods, such as reduced interaction and student engagement. This study recommends the development of more interactive online learning strategies to enhance their effectiveness.